Successful treatment of chromoblastomycosis using cryosurgery in association with low-dose itraconazole - Talira Caserta Gon; Trícia Caserta Gon; Airton dos Santos Gon (Surgical & Cosmetic Dermatology, 2023)
Chromoblastomycosis is a chronic granulomatous infection caused by dematiaceous fungi with varied clinical presentations, which may represent a therapeutic challenge. In this report, we present a case of chromoblastomycosis in a localized form, with a long evolution, in an elderly patient, resistant to previous drug therapies, successfully treated by the association of a physical method with systemic pharmacological treatment, which allowed the use of a reduced dose of the drug.